2019
DOI: 10.3390/w11102141
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Impact of Climate Change on the Hydrological Regimes of a Sparsely Gauged Mountainous Basin, Northern Pakistan

Abstract: Projected climate changes for the 21st century may cause great uncertainties on the hydrology of a river basin. This study explored the impacts of climate change on the water balance and hydrological regime of the Jhelum River Basin using the Soil and Water Assessment Tool (SWAT). Two downscaling methods (SDSM, Statistical Downscaling Model and LARS-WG, Long Ashton Research Station Weather Generator), three Global Circulation Models (GCMs), and two representative concentration pathways (RCP4.5 and RCP8.5) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…The JRB is characterized by highly heterogeneous soil and land cover; main types of soil include Gleyic Solonacks (49%), Calaric Phaoeozems soil (23%), and Mollic Planosols soil (21%). The basin drainage area is covered by diverse land cover such as agriculture (31%), grass-sparse vegetation (37%), forest (28%), water (2%) and settlement (2%) (Saddique et al 2019b).…”
Section: Description Of the Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The JRB is characterized by highly heterogeneous soil and land cover; main types of soil include Gleyic Solonacks (49%), Calaric Phaoeozems soil (23%), and Mollic Planosols soil (21%). The basin drainage area is covered by diverse land cover such as agriculture (31%), grass-sparse vegetation (37%), forest (28%), water (2%) and settlement (2%) (Saddique et al 2019b).…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…Based on the review literature and as far as the authors are aware, no previous study has been reported to date regarding LULC changes impact on the hydrology of the Jhelum River Basin (JRB). However, few studies (Mahmood andJia 2016 andSaddique et al 2019b) have assessed the impact of climate change on the stream flow of JRB forcing the Global Climate Models (GCMs) data. Therefore, this study filled this knowledge gap using different time periods land use data and employed SWAT hydrological model to simulate how these changes may affect the water resources of the basin.…”
Section: Introductionmentioning
confidence: 99%
“…To envisage the impact of climate change on sedimentation at the Mangla Dam, future projected hydrological data (2018-2100) of all the tributaries of the Mangla Reservoir under RCP4.5 and RCP8.5 by Naeem et al [22,32] were used in the numerical model as the upstream boundary condition. Naeem et al [22,32] conducted a study on the Mangla watershed and explored the impacts of climate change on Mangla Dam hydrology using the soil and water assessment tool (SWAT).…”
Section: River Flow Datamentioning
confidence: 99%
“…To envisage the impact of climate change on sedimentation at the Mangla Dam, future projected hydrological data (2018-2100) of all the tributaries of the Mangla Reservoir under RCP4.5 and RCP8.5 by Naeem et al [22,32] were used in the numerical model as the upstream boundary condition. Naeem et al [22,32] conducted a study on the Mangla watershed and explored the impacts of climate change on Mangla Dam hydrology using the soil and water assessment tool (SWAT). For assessing the climate change impacts on flow regimes for three future periods (2011-2040, 2041-2070, and 2071-2100), three Global Circulation Models (GCMs) (CanESM2, BCC-CSM1-1, and MICROC5), and two representative concentration pathways (RCP4.5 and RCP8.5) with two downscaling methods (Statistical Downscaling Model (SDSM) and Long Ashton Research Station Weather Generator (LARS-WG)).…”
Section: River Flow Datamentioning
confidence: 99%
See 1 more Smart Citation